The study of fresh baung fish quality (macron nemurus's ice) by using pakis vegetable (diplazium esculentum) As natural converser - OKTORIO '; MIRNA ILZA; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research is done to study quality of fresh baung fish with using of vegetable fern condensation as natural converser. Treatment which in giving is P0 (without of vegetable fern condensation, without salt), P1 (salt 2%), P2 (vegetable fern condensation) and P3 (vegetable fern condensation, salt 2%). As a group in along depository that is 0 hour, 4 hours, 8 hours, 12 hours]. converse of fresh fish the perceived is organoleptik value, ( face, smell, texture), total of bacterium colony, pH, Total Volatile Base. Value of fresh fish baung which given vegetable ferncondensation is added salt 2% with treatment of different is giving real influence to organoleptik value ( face, smell, texture), total value of colony, pH and TVB. Result of research seen from highest value of organoleptik is ( face 3,79, smell 3,54, texture 3,43), total of bacterium colony are 4,7 x 105 cell/ gram. The treatment is given by vegetable fern condensation added salt 2% during of depository at room temperature by value pH is 6,80 and TVB 12 mgn/ 100 gram.Keywords : Quality, baung fish (Macrones nemurus), vegetable fern (Diplazium esculentum), natural converser